Efficacy of pre and post-emergence herbicide on growth, yield and economics of sunflower (Helianthus annuus L.) under modified spacing: Efficacy of pre and post-emergence herbicide on growth, yield and economics of sunflower (Helianthus annuus L.) under modified spacing - K S SOMASHEKAR; G M SUJITH; M S UMA; K RAMESH; D NEHRU; K M SRINIVAS REDDY; C P MANJULA (Journal of Oilseeds Research, 2020)
Application of pendimethalin @ 1.0 kg a.i./ha as pre-emergence spray along with propaquizafop @ 62 g a.i/ha at 15-20 DAS as post emergent spray recorded significantly lower weed dry weight (53.5 g/m2 area), weed index (5.31) and higher weed control efficiency (89.1 %), seed yield (1728 kg/ha), head diameter (16.06 cm), test weight (6.06 g), gross returns (` 65,266), net returns (` 26,248) and B:C ratio (2.48).